2013
DOI: 10.1200/jco.2013.49.6968
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dense Temozolomide for Newly Diagnosed Glioblastoma: A Randomized Phase III Clinical Trial

Abstract: A B S T R A C T PurposeRadiotherapy with concomitant and adjuvant temozolomide is the standard of care for newly diagnosed glioblastoma (GBM). O 6 -methylguanine-DNA methyltransferase (MGMT) methylation status may be an important determinant of treatment response. Dose-dense (DD) temozolomide results in prolonged depletion of MGMT in blood mononuclear cells and possibly in tumor. This trial tested whether DD temozolomide improves overall survival (OS) or progression-free survival (PFS) in patients with newly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
626
5
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 878 publications
(659 citation statements)
references
References 21 publications
22
626
5
6
Order By: Relevance
“…PS and age are established prognostic factors for first-line as well as for second-line treatments [14,[32][33][34][35][36]. Recent studies set a threshold of KPS 60 % (corresponding to ECOG 2) as a prerequisite for tumour specific treatment interventions [4,5,37,38] as inferior PS is associated with increased side effects from any intervention and lowers the chance of clinical benefit [14,36,39]. The greatest consensus in our analysis was identified in unfit patients corresponding to a low PS.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…PS and age are established prognostic factors for first-line as well as for second-line treatments [14,[32][33][34][35][36]. Recent studies set a threshold of KPS 60 % (corresponding to ECOG 2) as a prerequisite for tumour specific treatment interventions [4,5,37,38] as inferior PS is associated with increased side effects from any intervention and lowers the chance of clinical benefit [14,36,39]. The greatest consensus in our analysis was identified in unfit patients corresponding to a low PS.…”
Section: Discussionmentioning
confidence: 63%
“…No consensus was obvious in all other occasions, despite approval and its steroid-sparing properties. The reason for this low overlap might be related to the absence of a controlled clinical trial for the use of bevacizumab in recurrent glioblastoma or the recently reported failure in the first-line treatment setting [4,38]. Moreover, conflicting results about a negative impact on neuro-cognition may also hamper widespread use of this compound [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It carries a very poor prognosis with mean overall survival of [12][13][14][15][16][17] months. Despite testing a multitude of chemotherapy agents and strategies, very little progress has been made in extending the life expectancy of those diagnosed with a GBM, since the establishment of the Stupp protocol (a combination of radiotherapy and temozolomide) a decade ago [2,3]. This is believed to be due to a high level of intrinsic drug resistance [4] combined with the fact that these tumours tend to diffusely invade the local brain parenchyma making it difficult to identify the perimeter and effectively remove them surgically [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…(4) In the hot spots of a tumor, the part of proliferant cells between tumor cells is of 20 to 30 % [47,54]. (5) Resistance mechanisms make the tumor start growing again after 6 to 8 month in the MTD protocol [27]. (6) Metronomic chemotherapies seem to be more efficient than MTD chemotherapies after 8 to 9 months [18].…”
Section: Parametrizationmentioning
confidence: 99%